PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN DAN KUALITAS INFORMASI AKUNTANSI TERHADAP KEEFEKTIFAN PENGENDALIAN INTERNAL PADA PT. PANDU SIWI SENTOSA (PANDU LOGISTIK) - OKY SYAHPUTRA; FHIKRY AHMAD HALOMOAN SIREGAR (LP2MTBM MAKARIOZ, 2022)
The aim in this study is to test and analyze the influence of accounting information systems (SIA) sales and the quality ofaccounting information on the effectiveness of internal controls. The selection of samples is done by convinience samplingmethod. The research population is the staff of sales accounting information system users and of 66 samples, 30 samplesare for validity and reliability testing and the remaining 36 samples for classical assumption testing, data analysis methodsand hypothesis tests. The study used multiple linear regression analysis for its statistical testing by conducting a classicalassumption test first. The results showed that simultaneously the Application of Sales Accounting Information System andQuality of Accounting Information had a positive and significant effect on the Effectiveness of Internal Control with a Fhinumeracy value of 80,846 with a significance of 0.000. Partially the Application of Sales Accounting Information System hasa positive and significant effect on the Effectiveness of Internal Control with a thitung value of 4,917 with a significance of0.000, while for the Quality of Accounting Information has a positive and significant effect on the Effectiveness of InternalControl with a thitung value of 3,060 with a significance of 0.000. The Effect of The Application of Sales AccountingInfoamation System and Information Quality on the Effectiveness of Internal Control simultaneously with a coefficient valueof R2 of 0.730 which means that in this study dependent variables can be explained by independent variables by 73%.